MORGAGNI HERNIA AS A DIFFERENTIAL DIAGNOSIS IN AN ADULT: A CASE REPORT - Nóbrega, Edgley Almeida; Araújo, Cicera Yolanda dos Santos; Araújo, Moisés Ederlânio Tavares de; Costa, Lineker Velozo; Gomes, Ana Karolynne de Souza; Torres, Larissa Moreira; Batista, Hermes Melo Teixeira (Amadeus International Multidisciplinary Journal, 2019)
Abstract: Morgagni Hernia (MH) is a defect between the transverse septum and the sternum, failing the fusion of the sternal and costal parts of the muscle, representing 3 to 4% of the hernia’s diaphragmatic lesions of congenital origin. It is present in 90% of the cases on the right side, 8% on the left side and 2% on the bilateral side. The aim of this article is to report a case on late presentation of MH and to emphasize the importance of this pathology to be analyzed with differential diagnosis in patients with respiratory symptoms. The subject is a patient, male, 62 years old, truck driver, married, with history of dyspnea on medium exertion and mild chest discomfort from 2 years. After 1 year of these symptoms, he evolved with major dyspnea on minor exertion, intense chest pain, without improvement with analgesics or with body positions, making it difficult to perform his usual activities as work and leisure. Multislice Computed Tomography of the Thorax, which showed: diaphragmatic hernia in the left hemithorax, with a ring/diaphragmatic fault located in the anterior and medial pericardial third, and an intrathoracic hernia, notably in the base and middle third in the anterior, lateral and posterior regions, with contents mesenteric and intestinal. The patient underwent thoracotomy in the sixth left intercostal space. A large amount of omentum, transverse colon, stomach, pulmonary atelectasis and small pleural effusion were found. The omentum resection was performed, located hernial ring in the antero-medial portion of the diaphragm, reduction of the hernia, placement of the Malex mesh and apposition of two anterior and posterior thoracic drains. Reports of patients initially diagnosed with pneumonia or treated as chronic dyspeptic, who progressed to intestinal necrosis, respiratory failure or other complications due to late diagnosis, emphasize the relevance of the knowledge of MH as a differential diagnosis of respiratory and gastrointestinal symptoms.